León Castillo, Janina y Javier M. Iguíñiz Echeverría (eds.). Desigualdad distributiva en el Perú: dimensiones. Lima: PUCP, Fondo Editorial, 2011. 324 pp. - Alvarez Ruíz, Lucciana (2012)
No presenta resumen